The Hotspots and Trends of Research on International The Sports industry from 2010-2019: A Visualization Analysis Based on Citespace - YuZhijiang ,Viktoriia Medvid (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
According to the collect and sort of relevant literature in the field of sports industry, the author found the continuity and correlation of current research themes, and the research trends in the next stage are incomplete and unclear. For the purpose to solve these problems and and explore the new direction of sports industry research, this paper processes the visualization analysis and statistics of co-cited references, co-cited author, keywords co-occurrence network and the bursting keywords through Citespace software and finds that the football industry, the fitness industry, sports media and sports tourism industry are the main hotspots and most of related research are from the prospective of sports marketing and management. More importantly, according to thekeyword co-occurrence network and the statistics of the bursting keywords, this paper believes that the research on women's sports is the frontier and will be another hotspot shortly.